Sb negative electrode material with excellent electrochemical performance and preparation method thereof
Patent Information
- Application Number
- CN202611240683.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-30
AI Technical Summary
但由于Sb2MoO6导电性较差,在充放电过程中体积变化剧烈,极易发生结构崩塌,导致循环稳定性较差,这极大限制了钼锑氧化物在二次电池中的应用
本发明提供了一种电化学性能优良的锑负极材料,通过引入形貌控制剂,成功制备了具有纳米棒状结构的Sb2MoO6。一维纳米结构能够为充放电过程中的巨大体积膨胀提供充足的径向缓冲空间,从而缓解了材料的粉化问题。聚苯胺原位聚合形成的均匀包覆层,经碳化后转变为氮掺杂的碳层,可有效缓冲体积变化、防止活性物质与电解液直接接触,并大幅提升电子导电性。本发明还创造性地将磷钼酸作为掺杂剂引入聚苯胺骨架,在后续热处理过程中,磷钼酸原位分解为具有电化学活性的MoP、Mo2C等纳米晶,同时实现磷原子对碳基质的掺杂,增加了大量界面储钠活性位点并催化了可逆转化反应。引入MXene作为外骨架,形成了三维互穿导电网络,提供了高速的电子和离子传输通道,显著改善了电化学性能。惰性气氛热处理过程中,聚苯胺碳化生成的碳基质和氮掺杂位点会与MXene表面的Ti原子发生反应,形成Ti-C或Ti-N化学键,同时发生碳相互扩散和融合,实现了碳包覆层与MXene导电骨架在界面处的化学键“焊接”。这种强界面结合确保了在长期循环体积反复膨胀收缩时,导电网络始终完整无脱落,这是实现卓越循环稳定性的核心机制之一。
Smart Images

Figure CN123017933A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery anode materials, specifically to an antimony anode material with excellent electrochemical performance and its preparation method. Background Technology
[0002] With the rapid expansion of the portable electronic device and electric vehicle markets, the demand for high-energy-density, long-cycle-life, and low-cost rechargeable batteries is becoming increasingly urgent. While lithium-ion batteries are widely used, the uneven distribution and rising costs of lithium resources have prompted researchers to focus on sodium-ion batteries, which are abundant and inexpensive. The anode material is one of the key factors determining battery performance. Among numerous candidate materials, metallic antimony has attracted considerable attention due to its high theoretical specific capacity, suitable sodium intercalation potential, and high tap density. However, elemental antimony undergoes significant volume changes during alloying / dealloying, leading to the pulverization of active material particles, detachment from the current collector, and repeated rupture and regeneration of the solid electrolyte interfacial film, ultimately resulting in irreversible capacity loss and rapid capacity decay.
[0003] Antimony molybdenum oxide (Sb₂MoO₆), as a typical mixed metal oxide, typically exhibits better electrochemical activity than elemental antimony and antimony oxides due to its complex composition, interfacial effects, and the synergistic effect of multiple metal active sites, thus showing promising application prospects as a negative electrode material for secondary batteries. Studies have shown that the excellent electrochemical performance of Sb₂MoO₆ is attributed to its novel layered structure and the synergistic interaction between active Sb and Mo species. However, due to its poor conductivity, Sb₂MoO₆ undergoes drastic volume changes during charge and discharge, making it prone to structural collapse and resulting in poor cycle stability. This significantly limits the application of Sb₂MoO₆ in secondary batteries. Summary of the Invention
[0004] Purpose of the invention: To address the above-mentioned technical problems, this invention proposes an antimony anode material with excellent electrochemical performance and its preparation method.
[0005] The technical solution adopted is as follows: A method for preparing an antimony anode material with excellent electrochemical performance includes the following steps: Preparation of Sb₂MoO₆ with a nanorod-like structure; Sb2MoO6 and phosphomolybdic acid were added to hydrochloric acid solution, and a suspension was obtained after ultrasonic vibration. Then, aniline and a free radical initiator were added, and the mixture was stirred to obtain polyaniline-coated Sb2MoO6. To prepare an MXene dispersion, polyaniline-coated Sb2MoO6 was added, and the mixture was ultrasonically vibrated before freeze-drying to obtain the precursor. The precursor can be heat-treated under argon protection.
[0006] This invention constructs a composite structure using the above steps, with nanorod-shaped Sb₂MoO₆ as the core, phosphomolybdic acid-doped and nitrogen-phosphorus co-doped carbon as a buffer layer, and MXene conductive nanosheets as the outer framework. Specifically, the nanorod-shaped structure ensures that the active material Sb₂MoO₆ has an inherent resistance to pulverization. Phospholybdic acid and aniline coexist in an acidic environment. The aniline monomer can be protonated, and the phosphomolybdic acid anion acts as a dopant, interacting electrostatically with the protonated aniline. When a free radical initiator is added, aniline polymerizes to form a polyaniline coating layer, with the phosphomolybdate ion uniformly incorporated as a dopant anion. The polyaniline-coated Sb₂MoO₆ is added to an MXene dispersion, and after ultrasonic vibration and freeze-drying, MXene nanosheets uniformly coat the exterior of the polyaniline layer, forming a core-shell structure. The heat treatment process under an inert atmosphere involves several key transformations: polyaniline is carbonized into nitrogen-doped amorphous carbon; phosphomolybdic acid decomposes and generates nanocrystals such as MoP and Mo2C in the surrounding carbon matrix, while phosphorus is partially doped into the carbon lattice. During this process, intense chemical bond breaking and recombination occur. The carbon matrix and nitrogen-doped sites generated by carbonization react with Ti atoms on the MXene surface to form Ti-C or Ti-N chemical bonds. Simultaneously, the carbon framework between the MXene layers and the carbon generated by polyaniline carbonization undergo interdiffusion and fusion at high temperatures. This tight bond constructed by chemical bonds ensures that electronic contact failure or detachment does not occur between the conductive frameworks during subsequent repeated charging and discharging and drastic changes in the volume of the active material. Electrons and ions can be rapidly and stably transported to each active particle through the chemically bonded interface, thus achieving high capacity retention.
[0007] Furthermore, the preparation method of the Sb2MoO6 is as follows: Molybdenum source, antimony source and morphology control agent are added to water, stirred evenly, and then transferred to a polytetrafluoroethylene-lined reactor. After sealing and hydrothermal reaction, the product is collected, washed and dried to obtain the final product.
[0008] Furthermore, the morphology control agent is a thiol-containing polycarboxylic compound.
[0009] Furthermore, the morphology control agent is thiomalic acid.
[0010] Morphology control agents are crucial for the final formation of nanorod morphology. Thiomalic acid contains both thiol and two carboxyl groups, which can strongly complex with metal ions under hydrothermal conditions and selectively adsorb onto specific crystal faces, driving anisotropic growth and forming nanorod-like structures.
[0011] Furthermore, the amount of the morphology control agent is 1%-10% of the mass of the molybdenum source.
[0012] Furthermore, the hydrothermal reaction temperature is 155-165℃, and the hydrothermal reaction time is 18-36h.
[0013] In this hydrothermal synthesis, the reaction temperature and time must be strictly controlled. If the temperature is below 155℃, the reactants will not transform completely, and the selective adsorption of the morphology control agent will be insufficient, resulting in impurities or irregular particles in the product. If the temperature is above 165℃, the nanorods will grow too quickly, their diameter will increase, and they may even form sintered agglomerates, losing their one-dimensional advantage. The optimal hydrothermal time is 18-36 hours. Insufficient time will result in incomplete crystallization, while excessive time may cause the nanorods to dissolve and recrystallize, leading to morphological damage. The most preferred hydrothermal conditions are a hydrothermal reaction at 160℃ for 24 hours.
[0014] Furthermore, the concentration of the hydrochloric acid solution is 0.5-1.5 mol / L.
[0015] Furthermore, the mass ratio of Sb2MoO6, phosphomolybdic acid, and aniline is 1:0.05-0.1:0.15-0.3.
[0016] Furthermore, the mass ratio of polyaniline-coated Sb2MoO6 to MXene is 1-4:1-4.
[0017] Furthermore, the heat treatment temperature is 650-750℃, and the heat treatment time is 2-4 hours.
[0018] The present invention also provides an antimony anode material with excellent electrochemical performance, which is specifically prepared by the above-described preparation method.
[0019] Beneficial effects This invention provides an antimony anode material with excellent electrochemical performance. By introducing a morphology control agent, Sb₂MoO₆ with a nanorod-like structure was successfully prepared. The one-dimensional nanostructure provides sufficient radial buffer space for the huge volume expansion during charge and discharge, thereby alleviating the pulverization problem of the material. The uniform coating layer formed by in-situ polymerization of polyaniline is transformed into a nitrogen-doped carbon layer after carbonization, which can effectively buffer volume changes, prevent direct contact between the active material and the electrolyte, and significantly improve electronic conductivity. This invention also creatively introduces phosphomolybdic acid as a dopant into the polyaniline framework. During subsequent heat treatment, phosphomolybdic acid decomposes in-situ into electrochemically active nanocrystals such as MoP and Mo₂C, while simultaneously achieving phosphorus atom doping of the carbon matrix, increasing a large number of interfacial sodium storage active sites and catalyzing the reversible reaction. The introduction of MXene as an exoskeleton forms a three-dimensional interpenetrating conductive network, providing high-speed electron and ion transport channels and significantly improving electrochemical performance. During inert atmosphere heat treatment, the carbon matrix and nitrogen-doped sites generated by the carbonization of polyaniline react with Ti atoms on the MXene surface to form Ti-C or Ti-N chemical bonds. Simultaneously, carbon interdiffusion and fusion occur, achieving a chemical bond "welding" between the carbon coating layer and the MXene conductive framework at the interface. This strong interfacial bonding ensures that the conductive network remains intact and does not detach during long-term cycling and repeated volume expansion and contraction, which is one of the core mechanisms for achieving excellent cycling stability.
[0020] The antimony anode material prepared in this invention shows broad application prospects in secondary batteries, especially sodium-ion batteries. Through structural design and multilayer composites, the intrinsic defects of Sb₂MoO₆, such as poor conductivity and large volume expansion, are overcome. With its ultra-long cycle life, high reversible capacity, and excellent rate performance, this material is very suitable as a long-life, low-cost anode for sodium-ion batteries, and can be applied to large-scale energy storage systems, low-speed electric vehicles, portable electronic devices, and other fields sensitive to cycle stability and cost. Furthermore, the preparation method is controllable, operates under mild conditions, and is easy to scale up, providing a feasible solution for the industrialization of next-generation high-performance alkali metal-ion battery anode materials. Attached Figure Description
[0021] Figure 1 This is a TEM image of Sb2MoO6 prepared in Example 1. Detailed Implementation
[0022] Unless otherwise specified in the examples, the conditions were performed under standard conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products. Techniques not mentioned in this invention refer to existing technologies. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0023] Example 1: An antimony anode material with excellent electrochemical performance and its preparation method: Weigh out 2.96g of (NH4)6Mo7O 24 4H₂O and 6g SbF₃ were dissolved in 300mL of deionized water and stirred until completely dissolved. Then, 0.1g thiomalic acid was added as a morphology control agent, and the mixture was stirred continuously for 30min to form a transparent solution. This solution was transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene (PTFE), sealed, and placed in an oven. The temperature was raised to 160℃ and maintained at a constant temperature for hydrothermal reaction for 24h. After the reaction was completed, the mixture was cooled to room temperature, and the product was centrifuged, washed three times with deionized water and anhydrous ethanol, and then vacuum dried at 80℃ for 12h to obtain Sb₂MoO₆ with nanorod-like structures. TEM images are shown below. Figure 1 .
[0024] 1 g of the above Sb₂MoO₆ and 0.08 g of phosphomolybdic acid were added to 100 mL of 1 mol / L hydrochloric acid solution and ultrasonically dispersed in an ice bath for 30 min to obtain a suspension. Then, 0.2 g of aniline monomer was slowly added dropwise while stirring in an ice bath, and stirring was continued for 30 min to allow aniline to fully adsorb with phosphomolybdic acid and Sb₂MoO₆. Next, 0.1 g of ammonium persulfate was added, and the reaction was maintained at 0-5℃ with stirring in an ice bath for 1 h. After removing the ice bath, the reaction was allowed to proceed at room temperature for 12 h. After the reaction was completed, the mixture was filtered, and the product was washed with deionized water and ethanol until the filtrate was colorless. The product was then vacuum dried at 60℃ for 12 h to obtain polyaniline-coated Sb₂MoO₆.
[0025] Weigh 1g of Ti3AlC2 powder and slowly add it to 20mL of 40% hydrofluoric acid. Stir and etch at 35℃ for 48h. Wash repeatedly with deionized water until pH=6. The resulting multilayer Ti3C2T... x Dispersed in 50 mL of deionized water, the particles were ultrasonically exfoliated under an argon atmosphere for 2 h, followed by low-speed centrifugation to remove unexfoliated particles, yielding Ti3C2T. x After freeze-drying the nanosheet dispersion at low temperature, take 0.25g of Ti3C2T x Add 50 mL of deionized water and sonicate to obtain a dispersion. Add 0.25 g of polyaniline-coated Sb₂MoO₆ to the above dispersion and sonicate in an ice bath for 30 min to obtain a mixed dispersion. Place the mixed dispersion in a freeze dryer and freeze-dry at low temperature to obtain the precursor. Place the precursor in a corundum ceramic boat, introduce high-purity argon gas into a tube furnace, heat to 700 °C at 3 °C / min, hold at this temperature for 3 h, and then allow to cool naturally to room temperature to obtain the final product.
[0026] Example 2: Basically the same as Example 1, except that 0.1g of Ti3C2T is used. xAdd 50 mL of deionized water and sonicate to obtain a dispersion. Add 0.4 g of polyaniline-coated Sb₂MoO₆ to the above dispersion and sonicate in an ice bath for 30 min to obtain a mixed dispersion. Place the mixed dispersion in a freeze dryer and freeze-dry at low temperature to obtain the precursor. Place the precursor in a corundum ceramic boat, introduce high-purity argon gas into a tube furnace, heat to 700 °C at 3 °C / min, hold at this temperature for 3 h, and then allow to cool naturally to room temperature to obtain the final product.
[0027] Example 3: Basically the same as Example 1, except that 0.4g of Ti3C2T is used. x Add 50 mL of deionized water and sonicate to obtain a dispersion. Add 0.1 g of polyaniline-coated Sb₂MoO₆ to the above dispersion and sonicate in an ice bath for 30 min to obtain a mixed dispersion. Place the mixed dispersion in a freeze dryer and freeze-dry at low temperature to obtain the precursor. Place the precursor in a corundum ceramic boat, introduce high-purity argon gas into a tube furnace, heat to 700 °C at 3 °C / min, hold at this temperature for 3 h, and then allow to cool naturally to room temperature to obtain the final product.
[0028] Example 4: Basically the same as Example 1, except that the heat treatment temperature is 750℃ and the heat treatment time is 2h.
[0029] Example 5: Basically the same as Example 1, except that the heat treatment temperature is 650℃ and the heat treatment time is 4h.
[0030] Example 6: This example is essentially the same as Example 1, except that 1g of the above-mentioned Sb₂MoO₆ and 0.1g of phosphomolybdic acid were added to 100mL of a 1mol / L hydrochloric acid solution and ultrasonically dispersed in an ice bath for 30min to obtain a suspension. Then, under stirring in an ice bath, 0.3g of aniline monomer was slowly added dropwise, and stirring continued for 30min to allow aniline to fully adsorb with phosphomolybdic acid and Sb₂MoO₆. Next, 0.1g of ammonium persulfate was added, and the reaction was maintained at 0-5℃ with stirring in an ice bath for 1h. After removing the ice bath, the reaction was allowed to proceed at room temperature for 12h. After the reaction was complete, the mixture was filtered, and the product was washed with deionized water and ethanol until the filtrate was colorless. The product was then vacuum dried at 60℃ for 12h to obtain polyaniline-coated Sb₂MoO₆.
[0031] Example 7: This example is essentially the same as Example 1, except that 1g of the above-mentioned Sb₂MoO₆ and 0.05g of phosphomolybdic acid were added to 100mL of a 1mol / L hydrochloric acid solution and ultrasonically dispersed in an ice bath for 30min to obtain a suspension. Then, under stirring in an ice bath, 0.15g of aniline monomer was slowly added dropwise, and stirring continued for 30min to allow aniline to fully adsorb with phosphomolybdic acid and Sb₂MoO₆. Next, 0.1g of ammonium persulfate was added, and the reaction was maintained at 0-5℃ with stirring in an ice bath for 1h. After removing the ice bath, the reaction was allowed to proceed at room temperature for 12h. After the reaction was complete, the mixture was filtered, and the product was washed with deionized water and ethanol until the filtrate was colorless. The product was then vacuum dried at 60℃ for 12h to obtain polyaniline-coated Sb₂MoO₆.
[0032] Comparative Example 1: It is basically the same as Example 1, except that phosphomolybdic acid is not added.
[0033] Comparative Example 2: It is basically the same as Example 1, except that it does not undergo a coating treatment, as detailed below: Weigh out 2.96g of (NH4)6Mo7O 24 • 4H₂O and 6g SbF₃ were dissolved in 300mL of deionized water and stirred until completely dissolved. Then, 0.1g of thiomalic acid was added as a morphology control agent, and the mixture was stirred continuously for 30min to form a transparent solution. This solution was transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, sealed, and placed in an oven. The temperature was raised to 160℃ and maintained at a constant temperature for hydrothermal reaction for 24h. After the reaction was completed, the mixture was cooled to room temperature, and the product was centrifuged. It was washed three times with deionized water and anhydrous ethanol, and then dried under vacuum at 80℃ for 12h to obtain Sb₂MoO₆ with nanorod-like structures.
[0034] Weigh 1g of Ti3AlC2 powder and slowly add it to 20mL of 40% hydrofluoric acid. Stir and etch at 35℃ for 48h. Wash repeatedly with deionized water until pH=6. The resulting multilayer Ti3C2T... x Dispersed in 50 mL of deionized water, the particles were ultrasonically exfoliated under an argon atmosphere for 2 h, followed by low-speed centrifugation to remove unexfoliated particles, yielding Ti3C2T. x After freeze-drying the nanosheet dispersion at low temperature, take 0.25g of Ti3C2T x Add 50 mL of deionized water and sonicate to obtain a dispersion. Add 0.25 g of Sb₂MoO₆ to the above dispersion and sonicate in an ice bath for 30 min to obtain a mixed dispersion. Place the mixed dispersion in a freeze dryer and freeze-dry at low temperature to obtain the precursor. Place the precursor in a corundum ceramic boat, introduce high-purity argon gas into a tube furnace, heat to 700 °C at 3 °C / min, hold at this temperature for 3 h, and then allow to cool naturally to room temperature to obtain the final product.
[0035] Comparative Example 3: It is basically the same as Example 1, except that the precursor is not heat-treated.
[0036] Comparative Example 4: The preparation method is basically the same as in Example 1, except that thiomalic acid is not added when preparing Sb2MoO6.
[0037] Performance testing: The materials prepared in the examples and comparative examples, conductive carbon black (Super-P), and sodium alginate binder were ground and mixed at a mass ratio of 8:1:1. A small amount of water was added and stirred to form a uniform slurry, which was then coated onto copper foil. After vacuum drying, the slurry was cut into pieces to serve as working electrodes. Using a sodium metal sheet as the counter electrode, 5% fluoroethylene carbonate was added to a 1 mol / L NaClO4 solution of ethylene carbonate / diethyl carbonate (volume ratio 1:1) as the electrolyte. CR2032 button cells were assembled in an argon-filled glove box. The CR2032 button cells were subjected to constant current charge-discharge tests using a LAND battery testing system. The voltage test range was 0.01V-3V, and the current density was 1A·g. -1 The test results are shown in Table 1 below; Table 1:
[0038] As shown in Table 1 above, the antimony anode material prepared by this invention has excellent electrochemical performance.
[0039] By comparing Example 1 with Comparative Example 1: Comparative Example 1 omitted phosphomolybdic acid. Due to the lack of active nanophases such as MoP / Mo2C generated by the in-situ decomposition of phosphomolybdic acid and the doping modification of the carbon layer by phosphorus, the sodium storage capacity of the material at the interface was greatly weakened, and the reversibility of the conversion reaction during the cycle was worse.
[0040] A comparison of Example 1 and Comparative Example 2 reveals that Comparative Example 2 completely skipped the polyaniline coating step, directly compositing Sb₂MoO₆ with MXene. During cycling, the active material lacked the buffer protection of an elastic carbon layer, and the significant volume change caused it to rapidly separate from the MXene conductive framework and pulverize. This clearly demonstrates that the carbon protective layer formed by in-situ polyaniline coating is a crucial element in the entire structural design.
[0041] By comparing Example 1 with Comparative Example 3: The precursor of Comparative Example 3 was not heat-treated. At this time, the polyaniline was not carbonized, the phosphomolybdic acid did not decompose to produce the active phase, and the chemical bonding interface between the carbon layer and MXene was not formed. Therefore, the electrochemical performance was poor. This strongly highlights the significance of the heat treatment step in "activating" the entire composite material and building a robust chemical bonding interface.
[0042] By comparing Example 1 with Comparative Example 4: Comparative Example 4 did not use thiomalic acid. Its product was random particles, and even with the same coating and composite modification, it would gradually pulverize and fail due to accumulated stress during long-term cycling because it did not have the one-dimensional volume buffering advantage of nanorods, resulting in significantly inferior performance.
[0043] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an antimony anode material with excellent electrochemical performance, characterized in that, Includes the following steps: Preparation of Sb₂MoO₆ with a nanorod-like structure; Sb2MoO6 and phosphomolybdic acid were added to hydrochloric acid solution, and a suspension was obtained after ultrasonic vibration. Then, aniline and a free radical initiator were added, and the mixture was stirred to obtain polyaniline-coated Sb2MoO6. To prepare an MXene dispersion, polyaniline-coated Sb2MoO6 was added, and the mixture was ultrasonically vibrated before freeze-drying to obtain the precursor. The precursor can be heat-treated under argon protection.
2. The method for preparing the antimony anode material with excellent electrochemical performance as described in claim 1, characterized in that, The preparation method of Sb2MoO6 is as follows: Molybdenum source, antimony source and morphology control agent are added to water, stirred evenly, and then transferred to a polytetrafluoroethylene-lined reactor. After sealing and hydrothermal reaction, the product is collected, washed and dried to obtain the final product.
3. The method for preparing the antimony anode material with excellent electrochemical performance as described in claim 2, characterized in that, The morphology control agent is a polycarboxylic compound containing a thiol group.
4. The method for preparing the antimony anode material with excellent electrochemical performance as described in claim 3, characterized in that, The morphology control agent is thiomalic acid.
5. The method for preparing the antimony anode material with excellent electrochemical performance as described in claim 2, characterized in that, The hydrothermal reaction temperature is 155-165℃, and the hydrothermal reaction time is 18-36h.
6. The method for preparing the antimony anode material with excellent electrochemical performance as described in claim 1, characterized in that, The concentration of the hydrochloric acid solution is 0.5-1.5 mol / L.
7. The method for preparing the antimony anode material with excellent electrochemical performance as described in claim 1, characterized in that, The mass ratio of Sb₂MoO₆, phosphomolybdic acid, and aniline is 1:0.05-0.1:0.15-0.
3.
8. The method for preparing the antimony anode material with excellent electrochemical performance as described in claim 1, characterized in that, The mass ratio of polyaniline-coated Sb2MoO6 to MXene is 1-4:1-4.
9. The method for preparing the antimony anode material with excellent electrochemical performance as described in claim 1, characterized in that, The heat treatment temperature is 650-750℃, and the heat treatment time is 2-4 hours.
10. An antimony anode material with excellent electrochemical performance, characterized in that, It is prepared by the preparation method of any one of claims 1-9.